Monolithic multilayer microfluidics via sacrificial molding of 3D-printed isomalt() - Gelber, Matthew K. (Lab Chip, 2015)
Here we demonstrate a method for creating multilayer or 3D microfluidics by casting a curable resin around a water-soluble, freestanding sacrificial mold. We use a purpose-built 3D printer to pattern self-supporting filaments of the sugar alcohol isomalt, which we then back-fill with a transparent epoxy resin. Dissolving the sacrificial mold leaves a network of cylindrical channels as well as input and output ports. We use this technique to fabricate a combinatorial mixer capable of producing 8 combinations of two fluids in ratios ranging from 1 : 100 to 100 : 1. This approach allows rapid iteration on microfluidic chip design and enables the use of geometry and materials not accessible using conventional soft lithography. The ability to precisely pattern round channels in all three dimensions in hard and soft media may prove enabling for many organ-on-chip systems.